Grafted double-charged composite nanofiltration membrane as well as preparation method and application thereof

By grafting the amination layer on the surface of the ultrafiltration base membrane and performing interfacial polymerization, a composite nanofiltration membrane with double charge characteristics was prepared, which solved the interception efficiency and adhesion problems of conventional nanofiltration membranes when dealing with complex water bodies, and achieved more Efficient ion removal and stability.

CN119186261APending Publication Date: 2024-12-27TIANJIN MOTIMO MEMBRANE TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411242887.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

When conventional polyamide composite nanofiltration membranes treat complex water bodies, it is difficult to efficiently intercept multivalent anions and multivalent cations at the same time, and the physical connection between the separation layer and the ultrafiltration substrate is not firm, resulting in easy shedding and degradation of separation performance.

Method used

By grafting a positively charged amination layer on the surface of the ultrafiltration base membrane, and applying an aqueous amino group solution to the surface, adding an oil-phase solution of polyfunctional acid chloride to the oil-phase solution for interfacial polymerization, the bottom positive charge and top negative charge are prepared. The double-charge composite nanofiltration membrane forms a separation layer connected by chemical bonds.

Benefits of technology

It improves the removal efficiency and water flux of the water neutral cations, enhances the adhesion firmness of the separation layer, and extends the service life and operation stability of the nanofiltration membrane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186261A_ABST
    Figure CN119186261A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of membrane separation, and particularly relates to a preparation method of a grafted double-charged composite nanofiltration membrane and application of the grafted double-charged composite nanofiltration membrane. The preparation method comprises the following steps: 1) grafting a positively charged amination layer on the surface of an ultrafiltration base membrane to obtain a functionalized base membrane; 2) coating the surface of the functionalized base membrane obtained in the step 1) with an amino aqueous solution; and (3) adding an oil-phase solution of polyfunctional acyl chloride, and carrying out interfacial polymerization to prepare the double-charge composite nanofiltration membrane. The separation layer of the grafted double-charged composite nanofiltration membrane obtained by adopting the technical scheme of the invention has a double-electric-layer structure of which the bottom is positively charged and the top is negatively charged, so that the removal efficiency of anions and cations in water can be improved, and the water flux can be improved; meanwhile, micromolecular polyamine grafted on the surface of the base membrane and trimesoyl chloride in the oil-phase solution are also subjected to cross-linking reaction, so that chemical bonding exists between the composite membrane separation layer and the base membrane, and correspondingly, the prepared separation layer can be more firmly attached to the surface of the base membrane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of membrane separation, and specifically relates to a grafted double-charged composite nanofiltration membrane and a preparation method and application thereof. Background Art

[0002] Membrane separation technology is widely used in water treatment, material separation, purification, concentration and other fields. At present, membrane technology has gradually replaced traditional water treatment processes due to its energy saving, high efficiency, simple process and convenient operation. Nanofiltration technology, as a kind of membrane separation technology, can effectively screen and intercept specific substances by using steric hindrance effect and charge repulsion effect. However, natural water bodies and industrial wastewater have complex compositions, and anionic and cationic substances usually exist in water bodies at the same time.

[0003] Conventional polyamide composite nanofiltration membranes only have a single charge characteristic. When treating complex water bodies, they are easily attacked by both positively and negatively charged pollutants, which greatly reduces the separation performance and service life of the nanofiltration membrane. Based on this, researchers proposed the concept of dual-charged composite nanofiltration membranes, that is, composite nanofiltration membranes whose separation layers have both positive and negative charge characteristics. The dual-charge characteristics enable the nanofiltration membrane to simultaneously produce charge repulsion with anions and cations in the water, thereby improving the separation effect.

[0004] Conventional interfacial polymerization process is a method for preparing nanofiltration and reverse osmosis membranes by directly coating an aqueous solution containing aqueous monomers (such as piperazine, diethylenetriamine, m-phenylenediamine, p-phenylenediamine, etc.) on the surface of an ultrafiltration membrane, and then performing interfacial polymerization reaction with an oil phase solution of trimesoyl chloride. However, the polyamide layer prepared by this method is physically connected to the ultrafiltration substrate, so the polyamide layer is not firmly attached to the surface of the ultrafiltration substrate and is easy to fall off. In addition, the polyamide nanofiltration membrane prepared by the conventional interfacial polymerization process is difficult to efficiently intercept multivalent anions and multivalent cations at the same time. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing a grafted dual-charged composite nanofiltration membrane and its preparation method and application.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A method for preparing a grafted dual-charged composite nanofiltration membrane comprises the following steps: 1) grafting a positively charged aminated layer onto the surface of an ultrafiltration base membrane to obtain a functionalized base membrane; 2) coating an amine aqueous solution on the surface of the functionalized base membrane obtained in step 1); 3) adding an oil phase solution of multifunctional acyl chloride to perform interfacial polymerization to prepare a dual-charged composite nanofiltration membrane.

[0008] The specific steps of step 1) are: circulating the polyamine aqueous solution into the membrane module tube to carry out a grafting reaction on the surface of the ultrafiltration base membrane, wherein the ultrafiltration base membrane is a base membrane containing a CCl bond; after the grafting reaction, removing the residual unreacted polyamine.

[0009] The temperature of the polyamine aqueous solution is 40-80°C, preferably 60°C.

[0010] The mass concentration of the polyamine is 0.25-2.0wt%; the polyamine is one of piperazine, diethylenetriamine, m-phenylenediamine, or p-phenylenediamine, or a mixture of at least two of them.

[0011] The specific steps of step 2) are: passing the amino aqueous phase solution into the tube side of the membrane component from bottom to top, and removing the excess aqueous phase solution after infiltration; preferably, the amino aqueous phase solution is a piperazine aqueous solution; preferably, the mass concentration of the piperazine aqueous solution is 0.1-2.0wt%; preferably 0.5wt%.

[0012] The specific steps of step 3) are: passing the oil phase solution of multifunctional acyl chloride into the tube side of the membrane component for interfacial polymerization reaction; preferably, the reaction time is 30-60s; preferably 50s; preferably, the multifunctional acyl chloride is one of trimesoyl chloride, adipoyl chloride, and sebacyl chloride; the solvent of the oil phase solution is one of n-hexane, cyclohexane, and heptane; the mass concentration of the oil phase solution is 0.1-0.25%; more preferably 0.15%.

[0013] In the base film containing CCl bonds, the base film is one of PVC, PVDF, PTFE, PVDF-CTFE, and CTFE.

[0014] The present invention also includes a grafted dual-charged composite nanofiltration membrane obtained by the preparation method.

[0015] The present invention also includes an application of the grafted dual-charged composite nanofiltration membrane, which is applied to water treatment, material separation, purification and concentration.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] The separation layer of the grafted dual-charged composite nanofiltration membrane obtained by adopting the technical solution of the present application has a double-layer structure with positive charge at the bottom and negative charge at the top, which can improve the removal efficiency of anions and cations in water and increase the water flux; at the same time, since the small molecule polyamine grafted on the surface of the base membrane can also undergo a cross-linking reaction with trimesoyl chloride in the oil phase solution, there is a chemical bond between the separation layer of the composite membrane and the base membrane, and accordingly, the prepared separation layer can be more firmly attached to the surface of the base membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a schematic diagram of the structure of the grafted dual-charged composite nanofiltration membrane of the present invention;

[0019] Figure 2 This is a comparison chart of the long-term operating stability of the composite nanofiltration membranes prepared in Comparative Example 1 and Example 2 of the present invention. DETAILED DESCRIPTION

[0020] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and the best embodiments.

[0021] Example 1

[0022] The preparation method of the grafted double-charged composite nanofiltration membrane includes the following steps: first, a 60°C 0.25wt% diethylenetriamine aqueous solution is circulated into the hollow fiber membrane module tube of the PVC ultrafiltration base membrane (the surface of the PVC ultrafiltration base membrane contains CCl bonds), and after the grafting reaction for 1 hour, it is rinsed with water to remove the residual unreacted polyamine. Then, a 0.5wt% piperazine aqueous phase solution is flowed from bottom to top into the tube of the PVC hollow fiber membrane module using a peristaltic pump. After soaking for 5 minutes, an air compressor is used to purge the membrane module tube from top to bottom at a linear speed of 13.0m / s to remove excess aqueous phase solution. The purge time is 5 minutes; then, a 0.15wt% trimesoyl chloride (TMC) / n-hexane solution is passed from bottom to top using a peristaltic pump and reacted for 50 seconds to prepare a hollow fiber polyamide nanofiltration membrane ( Figure 1 The schematic diagram of its structure is shown, including a base membrane 1, a grafted aminated layer 2 and a polyamide layer 3). After the experiment, the prepared nanofiltration membrane is stored in deionized water for testing.

[0023] Example 2

[0024] The preparation method of the grafted double-charged composite nanofiltration membrane includes the following steps: first, a 0.5wt% diethylenetriamine aqueous solution at 60°C is circulated into the tube side of the PVC hollow fiber membrane module, and after the grafting reaction for 1 hour, it is rinsed with water to remove the residual unreacted polyamine. Then, a 0.5wt% PIP aqueous phase solution is passed from bottom to top into the tube side of the PVC hollow fiber membrane module using a peristaltic pump. After soaking for 5 minutes, an air compressor is used to purge the membrane module tube side from top to bottom at a linear speed of 13.0m / s to remove excess aqueous phase solution, and the purge time is 5 minutes; then, a 0.15wt% trimesoyl chloride (TMC) / n-hexane solution is passed from bottom to top using a peristaltic pump, and the reaction is 50s to prepare a hollow fiber polyamide nanofiltration membrane. After the experiment, the prepared nanofiltration membrane is stored in deionized water for testing.

[0025] Example 3

[0026] The preparation method of the grafted double-charged composite nanofiltration membrane includes the following steps: first, a 60°C 1.0wt% diethylenetriamine aqueous solution is circulated into the hollow fiber membrane assembly tube, and after the grafting reaction for 1 hour, it is rinsed with water to remove the residual unreacted polyamine. Then, a 0.5wt% PIP aqueous solution is passed from bottom to top into the tube of the PVC hollow fiber membrane assembly by a peristaltic pump. After soaking for 5 minutes, an air compressor is used to purge the membrane assembly tube from top to bottom at a linear speed of 13.0m / s to remove excess aqueous solution. The purge time is 5 minutes; then, a 0.15wt% trimesoyl chloride (TMC) / n-hexane solution is passed from bottom to top by a peristaltic pump, and the reaction is performed for 50 seconds to prepare a hollow fiber polyamide nanofiltration membrane. After the experiment, the prepared nanofiltration membrane is stored in deionized water for testing.

[0027] Example 4

[0028] The preparation method of the grafted double-charged composite nanofiltration membrane includes the following steps: first, a 60°C 1.5wt% diethylenetriamine aqueous solution is circulated into the tube side of the PVC hollow fiber membrane module, and after the grafting reaction for 1 hour, it is rinsed with water to remove the residual unreacted polyamine. Then, a 0.5wt% PIP aqueous solution is passed from bottom to top into the tube side of the PVC hollow fiber membrane module using a peristaltic pump. After soaking for 5 minutes, an air compressor is used to purge the membrane module tube side from top to bottom at a linear speed of 13.0m / s to remove excess aqueous solution. The purge time is 5 minutes; then, a 0.15wt% trimesoyl chloride (TMC) / n-hexane solution is passed from bottom to top using a peristaltic pump, and the reaction is 50s to prepare a hollow fiber polyamide nanofiltration membrane. After the experiment, the prepared nanofiltration membrane is stored in deionized water for testing.

[0029] Example 5

[0030] The preparation method of the grafted double-charged composite nanofiltration membrane includes the following steps: first, a 60°C 2.0wt% diethylenetriamine aqueous solution is circulated into the tube side of the PVC hollow fiber membrane module, and after the grafting reaction for 1 hour, it is rinsed with water to remove the residual unreacted polyamine. Then, a 0.5wt% PIP aqueous solution is passed from bottom to top into the tube side of the PVC hollow fiber membrane module using a peristaltic pump. After soaking for 5 minutes, an air compressor is used to purge the membrane module tube side from top to bottom at a linear speed of 13.0m / s to remove excess aqueous solution. The purge time is 5 minutes; then, a 0.15wt% trimesoyl chloride (TMC) / n-hexane solution is passed from bottom to top using a peristaltic pump, and the reaction is 50s to prepare a hollow fiber polyamide nanofiltration membrane. After the experiment, the prepared nanofiltration membrane is stored in deionized water for testing.

[0031] Example 6

[0032] The preparation method of the grafted double-charged composite nanofiltration membrane includes the following steps: first, a 60°C 0.5wt% piperazine aqueous solution is circulated into the inner tube of the PVC hollow fiber membrane component, and after the grafting reaction for 1 hour, it is rinsed with water to remove the residual unreacted polyamine. Then, a 0.5wt% PIP aqueous phase solution is passed from bottom to top into the tube of the PVC hollow fiber membrane component by a peristaltic pump, and after soaking for 5 minutes, an air compressor is used to purge the membrane component tube from top to bottom at a linear speed of 13.0m / s to remove excess aqueous phase solution, and the purge time is 5 minutes; then, a 0.15wt% trimesoyl chloride (TMC) / n-hexane solution is passed from bottom to top by a peristaltic pump, and the reaction is 50s to prepare a hollow fiber polyamide nanofiltration membrane. After the experiment, the prepared nanofiltration membrane is stored in deionized water for testing.

[0033] Example 7

[0034] The preparation method of the grafted double-charged composite nanofiltration membrane includes the following steps: first, a 60°C 0.5wt% m-phenylenediamine aqueous solution is circulated into the tube side of the PVC hollow fiber membrane module, and after the grafting reaction for 1 hour, it is rinsed with water to remove the residual unreacted polyamine. Then, a 0.5wt% PIP mixed aqueous phase solution is passed from bottom to top into the tube side of the PVC hollow fiber membrane module using a peristaltic pump, and after soaking for 5 minutes, an air compressor is used to purge the membrane module tube side from top to bottom at a linear speed of 13.0m / s to remove excess aqueous phase solution, and the purge time is 5 minutes; then, a 0.15wt% trimesoyl chloride (TMC) / n-hexane solution is passed from bottom to top using a peristaltic pump, and the reaction is 50s to prepare a hollow fiber polyamide nanofiltration membrane. After the experiment, the prepared nanofiltration membrane is stored in deionized water for testing.

[0035] Comparative Example 1

[0036] The preparation method of conventional polyamide nanofiltration membrane comprises the following steps: first, a PIP aqueous solution with a concentration of 0.5wt% is passed from bottom to top through the tube side of the PVC hollow fiber membrane assembly by a peristaltic pump, and after soaking for 5 minutes, an air compressor is used to purge the membrane assembly tube side from top to bottom at a linear speed of 13.0m / s to remove excess aqueous solution, and the purge time is 5 minutes; then, a 0.15wt% trimesoyl chloride (TMC) / n-hexane solution is passed from bottom to top by a peristaltic pump, and the reaction is performed for 50 seconds to prepare a hollow fiber polyamide nanofiltration membrane. After the experiment, the prepared nanofiltration membrane is stored in deionized water for testing. Table 1 is a performance comparison table of nanofiltration membranes prepared by conventional interfacial polymerization process and double-charged composite nanofiltration membranes prepared by the present invention.

[0037] Table 1

[0038]

[0039] Result analysis:

[0040] Comparison between Example 2 and Comparative Example 1: After diethylenetriamine was grafted onto the surface of the PVC ultrafiltration membrane, diethylenetriamine could also participate in the interfacial polymerization reaction, resulting in an increase in the amount of amine groups participating in the reaction, and the formed polyamide cross-linked structure became looser, so that the pure water flux of the prepared nanofiltration membrane was significantly improved compared with that of Comparative Example 1, which was 15.3 L·m -2 ·h -1 bar -1 Moreover, due to the grafting of diethylenetriamine, the polyamide layer formed after interfacial polymerization has a dual charge characteristic, that is, the top of the polyamide layer has a negative charge characteristic and the back has a positive charge characteristic. As a result, compared with Comparative Example 1, the dual-charged composite nanofiltration membrane prepared in Example 2 exhibited a high MgCl2 retention rate of 95.7% and a high Na2SO4 retention rate of 97.3%.

[0041] Analysis of the results of Examples 1-5: As the concentration of grafted diethylenetriamine increases, the water flux of the prepared double-charged composite nanofiltration membrane shows a trend of first increasing and then decreasing. In detail, after the concentration of diethylenetriamine increases from 0.25wt% to 0.5wt%, the pure water flux of the nanofiltration membrane increases. This is because more amine groups participate in the reaction, and the formed polyamide composite structure becomes gradually loose. However, when the concentration of diethylenetriamine is further increased to 2.0wt%, the pure water flux of the prepared nanofiltration membrane begins to gradually decrease. This is because although the polyamide composite structure becomes looser, the thickness of the polyamide composite layer increases significantly, resulting in the pure water flux of the nanofiltration membrane still showing a downward trend. As for the salt retention rate, with the increase of the concentration of grafted diethylenetriamine, the positive charge on the back of the polyamide layer gradually increased, resulting in a gradual increase in the retention rate of MgCl2 by the prepared nanofiltration membrane. Due to the increase in the amount of amine groups participating in the reaction, the amount of residual acyl chloride after interfacial polymerization decreased, resulting in a weakening of the negative charge on the top of the prepared nanofiltration membrane. Therefore, the retention rate of Na2SO4 by the prepared nanofiltration membrane gradually decreased.

[0042] The results of Example 2, Example 6 and Example 7 show that when other polyamines, such as piperazine and m-phenylenediamine, are used instead of diethylenetriamine, doubly charged composite nanofiltration membranes can also be prepared, showing good ion retention performance and high pure water flux results.

[0043] like Figure 2As shown, compared with the conventional polyamide composite nanofiltration membrane of Comparative Example 1, the doubly charged composite nanofiltration membrane prepared by the present invention has better long-term operation stability because the polyamide layer and the ultrafiltration membrane are connected by chemical bonding. After 10 days of operation, the nanofiltration membrane still shows high and stable Na2SO4 retention rate and pure water flux results.

[0044] In summary, the separation layer of the grafted dual-charged composite nanofiltration membrane obtained by the technical solution of the present application has a double-layer structure with positive charge at the bottom and negative charge at the top, which can improve the removal efficiency of anions and cations in water and increase the water flux; at the same time, since the small molecule polyamine grafted on the surface of the base membrane also undergoes a cross-linking reaction with trimesoyl chloride in the oil phase solution, there is a chemical bond between the separation layer of the composite membrane and the base membrane, and accordingly, the prepared separation layer can be more firmly attached to the surface of the base membrane.

[0045] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a grafted dual-charged composite nanofiltration membrane, characterized in that: The method comprises the following steps: 1) grafting a positively charged aminated layer onto the surface of an ultrafiltration base membrane to obtain a functionalized base membrane; 2) coating an amine aqueous solution on the surface of the functionalized base membrane obtained in step 1); and 3) adding an oil phase solution of multifunctional acyl chloride to perform interfacial polymerization to prepare a dual-charged composite nanofiltration membrane.

2. The method for preparing the grafted dual-charged composite nanofiltration membrane according to claim 1, characterized in that: The specific steps of step 1) are: circulating the polyamine aqueous solution into the membrane module tube to carry out a grafting reaction on the surface of the ultrafiltration base membrane, wherein the ultrafiltration base membrane is a base membrane containing C-Cl bonds; after the grafting reaction, removing the residual unreacted polyamine.

3. The method for preparing the grafted dual-charged composite nanofiltration membrane according to claim 2, characterized in that: The temperature of the polyamine aqueous solution is 40-80°C, preferably 60°C.

4. The method for preparing the grafted dual-charged composite nanofiltration membrane according to claim 2, characterized in that: The mass concentration of the polyamine is 0.25-2.0wt%; the polyamine is one of piperazine, diethylenetriamine, m-phenylenediamine, or p-phenylenediamine, or a mixture of at least two of them.

5. The method for preparing the grafted dual-charged composite nanofiltration membrane according to claim 1, characterized in that: The specific steps of step 2) are: passing the amino-based aqueous solution into the tube side of the membrane component from bottom to top, and removing the excess aqueous solution after infiltration; preferably, the amino-based aqueous solution is a piperazine aqueous solution; preferably, the mass concentration of the piperazine aqueous solution is 0.1-2%; preferably 0.5%.

6. The method for preparing the grafted dual-charged composite nanofiltration membrane according to claim 1, characterized in that: The specific steps of step 3) are: passing the oil phase solution of multifunctional acyl chloride into the tube side of the membrane component for interfacial polymerization reaction; preferably, the reaction time is 30-60s; preferably 50s; preferably, the multifunctional acyl chloride is one of trimesoyl chloride, adipoyl chloride, and sebacyl chloride; the solvent of the oil phase solution is one of n-hexane, cyclohexane, and heptane; the mass concentration of the oil phase solution is 0.1-0.25%; more preferably 0.15%.

7. The method for preparing the grafted dual-charged composite nanofiltration membrane according to claim 2, characterized in that: In the base film containing C-Cl bonds, the base film is one of PVC, PVDF, PTFE, PVDF-CTFE, and CTFE.

8. A grafted dual-charged composite nanofiltration membrane obtained by the preparation method according to any one of claims 1 to 7.

9. An application of the grafted dual-charged composite nanofiltration membrane according to claim 8, characterized in that: Used in water treatment, material separation, purification and concentration.

Citation Information

Cited By

  • Nanofiltration membrane based on hydrophobic grafting interlayer modification as well as preparation method and application of nanofiltration membrane

    CN120305824A